The Effect of Educative Interaction Patterns of Religious Teachers on Student Learning Achievement - Muhammad Muslim; Indah Nurhidayati; Agus Fatuh Wardoyono (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
This study investigates the extent to which educative interaction patterns of Islamic education teachers influence students’ academic achievement in the Akidah Akhlak subject among ninth-grade learners at MTs Muhammadiyah 07 Klego Boyolali in the 2024/2025 academic year. Employing a quantitative survey design, data were collected through questionnaires and students’ report card documentation. Instrument validity was confirmed through corrected item–total correlation testing, while reliability reached a high level (Cronbach’s Alpha = 0.950). Descriptive analysis revealed that educative interaction quality fell within the moderate category (M = 64.38), as did student achievement (M = 85.7). Assumption tests confirmed normality (K–S = 0.757; p = 0.615) and a linear relationship between variables (p = 0.100). Regression analysis indicated a statistically significant effect of educative interaction patterns on academic achievement (t = −1.630; p = 0.030), with a coefficient of determination showing 64.3% of variance explained (R² = 0.643). These findings underscore the essential role of Islamic education teachers in shaping learning motivation and moral values, and they imply the need for strengthening interactive, humanistic pedagogical approaches in Islamic secondary schools.